Awareness Regarding Hypertension among Adults in a Community of Bhaktapur, Nepal - Pokhrel, Sanju; KC, Tulza (Journal of Institute of Medicine Nepal, 2019)
Introduction Hypertension is a common global health problem with significant morbidity and mortality. Various preventive life style practices play significant role in controlling it. The objective of this study was to identify awareness regarding hypertension among the adult people in a community of Bhaktapur, Nepal. Methods A descriptive cross-sectional study was conducted among 138 adults aged 20-59 residing in Bhaktapur, selected through non probability purposive sampling technique. The data was collected by face to face interview method through semi structured questionnaire. Data was analyzed by using descriptive and inferential statistics. Results The study showed that 58.7% of adults had adequate awareness regarding hypertension. About 35.5% knew the range of value of high blood pressure and nearly half (47.8%) answered heart as the organ primarily related to hypertension. Stress was identified as a risk for hypertension by 96.4%, 92% specified headache as main symptom and only 31.9% knew about the asymptomatic nature of hypertension. Nearly 90% were aware that management of hypertension includes all: medicine, diet and exercise. Almost 99% of the respondents mentioned about restricting alcohol for BP control and 93.2% mentioned heart attack as the complication of hypertension. Conclusion The study concluded that only half of adults have adequate awareness regarding hypertension. It also showed that there is statistically significant association of awareness level with age, religion, educational status, occupation, economic status, family history and diagnosis of hypertension. Thus, it could be recommended that health personnel should provide education and information covering all aspects of hypertension to adults residing in community.